2014
DOI: 10.1088/0960-1317/24/6/065012
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatic micro-actuator with a pre-charged series capacitor: modeling, design, and demonstration

Abstract: As a powerful method to reduce actuation voltage in an electrostatic micro-actuator, we propose and investigate an electrostatic micro-actuator with a pre-charged series capacitor. In contrast to a conventional electrostatic actuator, the injected pre-charges into the series capacitor can freely modulate the pull-in voltage of the proposed actuator even after the completion of fabrication. The static characteristics of the proposed actuator were investigated by first developing analytical models based on a par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“… 33 As aforementioned, acoustic microfluidic methods can be integrated with other microfluidic designs for enhanced fluid and particle manipulation performance. 34 36 For example, Huang et al. achieved dynamic manipulation of micro-objects by combining hydrodynamic manipulation and acoustic microfluidic manipulation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 33 As aforementioned, acoustic microfluidic methods can be integrated with other microfluidic designs for enhanced fluid and particle manipulation performance. 34 36 For example, Huang et al. achieved dynamic manipulation of micro-objects by combining hydrodynamic manipulation and acoustic microfluidic manipulation.…”
Section: Introductionmentioning
confidence: 99%
“…Zhao et al demonstrated the pumping of water droplets based on capillary force and developed and employed structural color micromotors (SCMs) that could realize multiplex label-free detection of ions based on their optical coding capacity and responsive behaviors . As aforementioned, acoustic microfluidic methods can be integrated with other microfluidic designs for enhanced fluid and particle manipulation performance. For example, Huang et al. achieved dynamic manipulation of micro-objects by combining hydrodynamic manipulation and acoustic microfluidic manipulation. They developed acoustic circulating tumor cell (CTC) separation devices integrating hydrodynamics and IDT and isolated rare CTCs from peripheral blood in a single direction; Zhou et al presented a rapid and powerful method to size dependently control movement of microparticles and cells in paper using surface acoustic waves by combining paper-based microfluidics with acoustics .…”
Section: Introductionmentioning
confidence: 99%